2016
DOI: 10.1057/palcomms.2015.46
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, the Great Barrier Reef and the response of Australians

Abstract: Inspiration, aspirations, attitudes, and perception of threats play a pivotal role in the way that individuals associate themselves with natural environments. These sentiments affect how people connect to natural places, including their behaviours, perceived responsibility, and the management interventions they support. World Heritage Areas hold an important place in the lives of people who visit, aspire to visit, or derive a sense of security and well-being from their existence. Yet, the connection between pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 66 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…For example, Turner et al (2016) have reinterpreted the data to assess how trust, confidence and equity affect legitimacy. Goldberg et al (2016) similarly reviewed the data to more fully describe the response of Australians to climate change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Turner et al (2016) have reinterpreted the data to assess how trust, confidence and equity affect legitimacy. Goldberg et al (2016) similarly reviewed the data to more fully describe the response of Australians to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Case study context: the Great Barrier Reef and its management The Great Barrier Reef Marine Park is widely regarded as one of the most sophisticated and well-resourced natural resource management settings in the world (figure 1). The Great Barrier Reef supports a wealth of economic activity ($5 billion per year) and is a vital contribution to the wellbeing of coastal communities (Larson et al 2013, Stoeckl et al 2011, Australians more generally (Goldberg et al 2016), and broader international community. The long term implications of climate change, poor water quality and coastal development have emerged as key sources of uncertainty and community expectations around each of these management challenges is high (Goldberg et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Public affinity for the GBR drove decision makers to protect the ecological values of the region during this period, culminating in the enactment of the Great Barrier Reef Marine Park Act 1975, a parliamentary Act designed to provide legislative support for core environmental values. Although Australians regard the GBR as one of the most inspiring landscapes in their nation (Goldberg et al 2016), recent ecological monitoring suggests that the reef system has suffered a 50% decline in hard coral cover since 1975 as a combined result of impacts from poor water quality, cyclones, crown-of-thorns starfish (Acanthaster planci) outbreaks, and a series of coral bleaching events (De'ath et al 2012). The cultural impacts that these changes are having are as yet unknown, and coastal development proposals continue to be a contentious aspect of GBR management.…”
Section: The Gbr Marine Parkmentioning
confidence: 99%
“…The Great Barrier Reef, for instance, is under immense environmental pressure as described in the next section, and it is valued globally (it is a World Heritage Site, after all) and by domestic Australians for its cultural and ecological significance. Goldberg et al [36] (p. 1) conducted a recent survey of domestic Australians and concluded that "climate change is perceived to be the biggest threat to the Great Barrier Reef, and that the Great Barrier Reef inspires Australians, promotes pride, and instills a sense of individual identity and collective responsibility to protect it". Should such sites and the experiences they offer to domestic and international visitors merely be destinations to "play" in, or should they also be places of pedagogy, contributing to environmental literacy, fostering global environmental citizenship and climate action to conserve them for current and future generations of residents and visitors?…”
Section: Information Deficit and Visitor (In)actionmentioning
confidence: 99%